PENGARUH PENERAPAN E-FILLING DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Rifani Akbar Sulbahri; Gumulya Sonny Marcel Kusuma (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
The objective of the research was to examines the influence of implementation of e-filling and tax sanctions on the individual taxplayer compliance with taxation socialization as a moderating variable. This research using primary data uses convenience sampling technique to select the respondent . Data were collected through a survey on 100 respondents individual taxplayer at KKP Ilir Timur of Palembang. Structural Equation Model with PLS was applied to analyzed the data. The result of this research indicate significant influence tax sanctions on the individual taxplayer compliance, and taxation socialization as a moderating variable. Futhermore, it was found that there were no significant influence implementation of e-filling on the individual taxplayer compliance. and taxation socialization as a moderating variable Keywords: implementation of E-filling, Tax Sanctions, Taxation Socialization, Individual Taxplayer Compliance